The intergenerational causal effect of tax evasion: Evidence from the commuter tax allowance in Austria - Wolfgang Frimmel; Martin Halla; Jörg Paetzold (Johannes Kepler University of Linz, Department of Economics, 2017)
Does tax evasion run in the family? To answer this question, we study the case of the commuter tax allowance in Austria. This allowance is designed as a step function of the distance between the residence and the workplace, creating sharp discontinuities at each bracket threshold. The distance to these brackets is a strong determinant of compliance since it corresponds to the probability of detection. The match of different administrative data sources allows us to observe actual compliance behavior at the individual level across two generations. To identify the intergenerational causal effect in tax evasion behavior, we use the paternal distance-to-bracket as an instrumental variable for paternal compliance. We find that paternal noncompliance increases children's non-compliance by about 20 percent.
Keywords: H26; A13; H24; J62; D14; 330; tax evasion; tax morale; intergenerational correlation; intergenerationalcausal effect